Investment Currency Risk and Methods of Reduction - Nedzveckas, Jonas; Rasimavičius, Gediminas (Ekonomika, 2000)
The article deals with the problem of investment and foreign investment currency risk. Shortly reviewed foreign investment in Lithuania. In Lithuania not enough local Lithuanian investors, because there is nu much investment capital potential. Lithuania institutional investors isn’t prepared to invest in security market. So in this topic we revise possibility of investment from foreign more advanced countries. In this chapter it is explained profit and risk of foreign investment. There are explained investment currency risk and methods of reduction, such as the diversification and currency derivatives and hedging (futures, forward and etc.). The power of diversification in reducing risk is widely practiced by investors. In recent years investors have been turning to foreign markets to obtain even greater scope for diversification than in possible in a domestic market. With the internationalization of security portfolios, however, also comes an additional risk - foreign exchange risk. Foreign exchange rate fluctuations induce changes in portfolio returns because uncertain future exchange rates translate returns on foreign-currencydenominated investment into local currency returns. Diversification of portfolio holdings across several countries can help mitigate foreign exchange risk. Hedging currency and securities are instruments that alter the cash flows of portfolio. The use of currency hedging can further reduce risk in internationally diversified portfolios.